Topical Ocular Drug Delivery: The Impact of Permeation Enhancers - Gonçalo Santos; Esmeralda Delgado; Beatriz Silva; Berta São Braz; Lídia Gonçalves (Pharmaceutics)
Topical ophthalmic drug delivery targeting the posterior segment of the eye has become a key area of interest due to its non-invasive nature, safety, ease of application, patient compliance, and cost-effectiveness. However, achievement of effective drug bioavailability in the posterior ocular segment is a significant challenge due to unique ocular barriers, including precorneal factors and anatomical barriers, like the cornea, the conjunctiva, and the sclera. Successful ocular drug delivery systems require increased precorneal residence time and improved corneal penetration to enhance intraocular bioavailability. A promising strategy to overcome these barriers is incorporating drug penetration enhancers (DPEs) into formulations. These compounds facilitate drug delivery by improving permeability across otherwise impermeable or poorly permeable membranes. At the ocular level, they act through three primary mechanisms: breaking tear film stability by interfering with the mucous layer; disrupting membrane components such as phospholipids and proteins; and loosening epithelial cellular junctions. DPEs offer significant potential to improve bioavailability and therapeutic outcomes, particularly for drugs targeting the posterior segment of the eye. This review is focused on analyzing the current literature regarding the use of penetration enhancers in topical ocular drug delivery, highlighting their mechanisms of action and potential to revolutionize ophthalmic treatments.